The extent to which Islamic studies teachers in Makkah Al-Mukarramah practice the dimension of digital respect in achieving intellectual security for secondary school female students from the teachers' point of view: - Alhashmi, Nidaa Adeel; Akram, Hubah Ahmad (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to identify the extent to which Islamic Studies teachers in Makkah Al-Mukarramah practice the dimension of digital respect in achieving intellectual security for secondary school female students from the teachers' point of view. The study adopted the descriptive approach using the survey method, and the questionnaire was used as a tool distributed to a random sample of (212) teachers. The results of the study showed that Islamic Studies teachers' awareness of the dimension of digital respect in achieving intellectual security had an overall average of (4.51 out of 5), which is a (very large) level. The results also showed the presence of statistically significant differences at a significance level of (α≤0.05) between the averages of Islamic Studies teachers regarding their awareness of the dimension of respect as one of the dimensions of digital citizenship practices in achieving intellectual security; attributed to the difference in years of experience, and these differences were in favor of teachers with (more than 10 years) of experience. The study recommended the importance of teachers' awareness and attention to the dimensions of digital citizenship in achieving intellectual security, represented by the dimension of respect. In light of the results, the study recommended the necessity of raising awareness of Islamic Studies teachers about the dimension of respect in achieving intellectual security and holding training courses for this purpose.
Keywords: Practice; Islamic Studies; Dimensions of Digital Citizenship; Intellectual Security